2021
DOI: 10.1111/myc.13384
|View full text |Cite
|
Sign up to set email alerts
|

Invasive aspergillosis in relapsed/refractory acute myeloid leukaemia patients: Results from SEIFEM 2016‐B survey

Abstract: Background: In patients with relapsed/refractory acute myeloid leukaemia (R/R AML) who received salvage chemotherapy, limited and not updated studies explored the incidence of invasive aspergillosis (IA) and the role of antifungal prophylaxis (AP). The aims of this multicentre retrospective 'SEIFEM 2016-B' study were as follows: (1) to evaluate the current rate and the outcome of proven/probable IA and (2) to assess the efficacy of AP, in a large 'real life' series of patient with R/R AML submitted to salvage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These findings are appreciable, thus suggesting that a broad-spectrum AFP may reduce the burden of IFDs, resulting in less severe forms. Previous studies reported a similar positive effect of AFP on the effectiveness of AFT [64,103]. Even if our first-line AFT did not comply with most guidelines, by favoring an antifungal of a different class [104][105][106][107][108], the treatment success was favorable, underlying how the optimal management of b-IFDs is largely unknown and the clinical studies investigating different treatment modalities are scarce [106,[109][110][111].…”
Section: Resultsmentioning
confidence: 71%
“…These findings are appreciable, thus suggesting that a broad-spectrum AFP may reduce the burden of IFDs, resulting in less severe forms. Previous studies reported a similar positive effect of AFP on the effectiveness of AFT [64,103]. Even if our first-line AFT did not comply with most guidelines, by favoring an antifungal of a different class [104][105][106][107][108], the treatment success was favorable, underlying how the optimal management of b-IFDs is largely unknown and the clinical studies investigating different treatment modalities are scarce [106,[109][110][111].…”
Section: Resultsmentioning
confidence: 71%